Leaderlessness in social movements: Advancing space, symbols, and spectacle as modes of "Leadership". (9th October 2021) - Keshtiban, Amir E.; Callahan, Jamie L.; Harris, Martin
Abstract: The emergence of the Occupy movements along with other social movements in 2011 elevated the idea of radically decentralized "leaderless" social movement organizations. We argue that looking at such an alternative, horizontalist form of organizing presents an opportunity to reframe how we understand leadership. This paper illustrates how the coordination of the Occupy London movement was accomplished horizontally in the absence of formal organization, leadership, or authority structures. Using an ethnographic approach, we show how this movement generated a "multimodal" repertoire of protest that included (1) the politically effective occupation of urban space ; (2) the ability to deploy symbols as compelling forms of aesthetic questioning; and (3) the creation of politically charged spectacles that allowed the movement to appropriate the news agendas of established broadcast media. The findings of this paper challenge the language of leadership and contribute to understandings of feminist forms of leadership and leaderless organizing by explaining one way that "leadership" occurs in horizontal organizational structures such as social movements. Namely we demonstrate how the modes of space, symbols, and spectacles effectively replace the role of "leader" in the absence of formal organizational structures.